2005
DOI: 10.5902/198050981831
|View full text |Cite
|
Sign up to set email alerts
|

Análise da mortalidade de <i>Acacia mearnsii</i> De Wild.

Abstract: A mortalidade de povoamentos de Acacia mearnsii De Wild. foi estudada tomando por base parcelas permanentes estratificadas em diferentes espaçamentos e sítios. Os resultados permitiram concluir que a probabilidade de mortalidade (PM) pode ser estimada por meio de uma função probabilística em relação ao inverso do diâmetro à altura do peito (d) e da idade (t): PM = {1+ EXP (-9,5593 . d-1 + 104,9543 . t-1)}-1. Mediante a correlação de Pearson, verificou-se uma alta associação entre a taxa de mortalidade com a id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
2
1
0
4
Order By: Relevance
“…These results clearly show that higher density initial spacing establishment presents higher mortality than lower densities. Higher mortality proportions found under higher density stands is consistent with other studies, such as Schneider et al (2005) and Leite et al (2006). This can be attributed to the lower competition suffered by trees under low densities.…”
Section: Mortalitysupporting
confidence: 92%
“…These results clearly show that higher density initial spacing establishment presents higher mortality than lower densities. Higher mortality proportions found under higher density stands is consistent with other studies, such as Schneider et al (2005) and Leite et al (2006). This can be attributed to the lower competition suffered by trees under low densities.…”
Section: Mortalitysupporting
confidence: 92%
“…The results of the present study are consistent with the finding of Schneider et al (2005), who found that mortality of other species of the Acacia genus was highly correlated to the traits of growth, with values of Pearson correlation coefficients varying from 0.49 to 0.73. In the present study, survival had a weak association with growth (measured by the rankings); although high values of prediction for Murchinson River in El Tangue, indicate the possibility of joint selection mechanisms between both traits.…”
Section: Resultssupporting
confidence: 93%
“…In the present study, survival had a weak association with growth (measured by the rankings); although high values of prediction for Murchinson River in El Tangue, indicate the possibility of joint selection mechanisms between both traits. This result is relevant for this improvement program with A. saligna, as the genetic association between the growth rate and resistance to drought tends to be scarce, according to the studies by Coyle et al (2006) and Schneider et al (2005).…”
Section: Resultsmentioning
confidence: 94%
“…Segundo Schneider et al (2005), agentes secundários como local, idade da árvore, espaçamento e condições climáticas influenciam a sobrevivência das árvores. A perda substancial em volume por árvore, na idade final, foi o que resultou em elevadas perdas na produção aos 92 meses.…”
Section: Modelounclassified